Violation of Human Rights by Acts of Corruption - Bonini, Márcio (Instituto de Estudios Avanzados - Universidad de Santiago de Chile, 2019)
This article aims to analyze the relationship between corruption and its violation and impact of Human Rights. The following itinerary, in a first moment, contextualizes some academic debates about how corruption has presented itself as a historical, sociological phenomenon and in the field of political science, in a multidisciplinary perspective. Secondly, a brief approach will be taken in the perspective of Hannah Arendt’s political philosophy about Human Rights and their contexts in the history of humanity, as well as their importance in the face of the atrocities promoted by totalitarian regimes in the early twentieth century. Finally, the aspects related to the material possibilities of violation of Human Rights and the phenomenon of corruption will be analyzed and to what extent would there be a causal link between corrupt practices and their potential to violate, in a right or indirect way, a right or how acts of corruption can lead to such violations.